EFEKTIVITAS LEMBAR KERJA MAHASISWA (LKM) TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS MAHASISWA - sri rezeki; Rahmawati Yuliyani; Bayu Jaya Tama (Jurnal THEOREMS (The Original Research of Mathematics), 2022)
This study aims to examine the effectiveness of the use of Student Worksheets on students' mathematical understanding abilities. The research subject is a private university in East Jakarta. The sampling technique used was purposive sampling with a sample of two classes, namely the experimental class and the control class. Data analysis was carried out quantitatively. The statistical test used was the Kolmogorov-Smirnov Z test for the normality test with the test results not being normally distributed. Meanwhile, for the average difference test, the Mann-Whitney non-parametric test was used with the test results that there were differences in results between the experimental class and the control class, then for the average, variance and range of the experimental class, namely 87.57; 196.14 and 40. Meanwhile, the average, variance and range of the control class were 79.29 ; 335,513 and 60. From this it can be seen that the average of the experimental class is higher than the control class, and the variance and range of the experimental class is smaller than the control class, this means that the experimental class is more homogeneous than the control class so it can be concluded that the students' mathematical understanding ability learning using the LKM is more effective than students who learn without using the LKM.